India's urban landscape; black towns of the 21st century - Khosla, Romi (2017)
The new Indian urban landscape is being designed around grand concepts such as smart cities and export-oriented industrial corridors. In our desire to be global, we are emulating outdated models of urbanisation and economic progress borrowed from nations that have grown rich through questionable means. Our cities remain bloated extensions of the early capitalist, modern European city, dogged by poverty and the concentration of wealth. We need to search for a future from our own capabilities and geographies. - Reproduced.
Keywords: Landscape design - India; Landscape design